The Implementation Of The Care-Protect (Pedulilindungi) Application: The Economic Impact And Constraints Faced - Franciskus Antonius Alijoyo; Erna Haerani (Green Publisher Indonesia, 2022)
The COVID-19 pandemic has harmed the global economy. This is due to the imposition of restrictions on social activities, which have a negative impact on employment and subsequently harm people's income and purchasing power. For this reason, the government has issued Care-Protect (PeduliLindungi) application, which functions to ensure that everyone active outside the house has been vaccinated and is free from the virus. This study aims to analyze the impact of the implementation of the PeduliLindungi application on community and economic activities in Indonesia and the obstacles faced in its implementation. This research was carried out by following a systematic literature review research method. The data were collected from previous studies that examined the enforcement of PeduliLindungi applications. The data were collected from the research results in articles published in Sinta indexed journals. The collected data is then analyzed using an interactive data analysis model. The results of this study indicate that the PeduliLindungi application has some impacts on the people's economy in Indonesia. In addition, this research also identifies several obstacles faced by the community and the government in implementing the PeduliLindungi application. Detailed results regarding the positive and negative impacts and constraints are discussed in this article, and some suggestions based on the findings are also presented.